Regional Economic Growth and Convergence in the Philippines: 1975-1997 - Rosario G. Manasan; Ruben G. Mercado (Philippine Institute for Development Studies (PIDS), 1999)
This study is a quantitative assessment of regional development performance in terms of economic growth and convergence (described simply as the minimization of disparities in regional income) during the period 1975-1997. The study not only takes stock of how far the goals of regional development have been achieved but also reflects on how development strategies, particularly taking the NIChood path of rapid GDP growth via industrialization, contribute to regional convergence or divergence. The results of the study indicated that marked disparities across regions still persist throughout 1975-1997. However, analysis of convergence revealed a decline in cross-regional dispersion of per capita income which has been seen to occur more rapidly from 1975-1986, a period of declining GDP growth rate than in 1987-1997, a period of accelerated GDP growth. This finding is consistent with the experience of other Asian countries including Malaysia and Thailand where a positive relationship was found between regional dispersion and the growth rate of GDP. In these economies, high growth was largely driven by accelerated industrialization. It, therefore, provides caution that high levels of economic growth (especially where it is led by the rapid expansion of the industry sector) may bring with it risks of regional stagnation, slow regional convergence or even divergence. In this sense, this finding emphasizes the possible tension between NIC-hood and regional convergence. The study concludes with a roadmap that shows the way towards a reconciliation of the two goals of regional development: to promote the reduction of regional disparity and to enhance accelerated growth of the national economy.
Keywords: 330; economic recovery